2001
DOI: 10.1139/g01-030
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of QTLs for salt tolerance during vegetative growth in tomato by selective genotyping

Abstract: The purpose of this study was to identify quantitative trait loci (QTLs) for salt tolerance (ST) during vegetative growth (VG) in tomato by distributional extreme analysis and compare them with the QTLs previously identified for this trait. A BC1 population (N = 792) of a cross between a moderately salt-sensitive Lycopersicon esculentum Mill. breeding line (NC84173, maternal and recurrent parent) and a salt-tolerant L. pimpinellifolium (Jusl.) Mill. accession (LA722) was evaluated for ST in solution cultures c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…(2005) found that the most tolerant genotypes of S. lycopersicum could be characterized by increased K + /Na + ratios, carotenoid and sucrose contents and a reduced level of lipid peroxidation in the leaves during salt stress, suggesting a central role of the photosynthetic performance in the selection and breeding of cultivars for salt tolerance, though many genes and QTLs have also been described (Foolad et al, 2001;Cuartero et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…(2005) found that the most tolerant genotypes of S. lycopersicum could be characterized by increased K + /Na + ratios, carotenoid and sucrose contents and a reduced level of lipid peroxidation in the leaves during salt stress, suggesting a central role of the photosynthetic performance in the selection and breeding of cultivars for salt tolerance, though many genes and QTLs have also been described (Foolad et al, 2001;Cuartero et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Co-localization of some QTLs for salt tolerance during seed germination and the seedling stage would strengthen the evidence that the same genes might control the rate of seed germination and seedling growth. Crosstalk for response to adverse abiotic and biotic stressors may share the common pathway, in which secondary metabolisms make a significant contribution (Chinnusamy et al Foolad et al 2001). Gray vertical bar indicate the approximate locations of QTLs previously identified from S. pennellii LA716 population for salt tolerance during seed germination (renamed as Stsgq) .…”
Section: Comparative Analysis Of Qtls For Abiotic Stressmentioning
confidence: 99%
“…Rapid progress in molecular marker technology over the past few years has led to the development of detailed molecular linkage maps for many plant species (Jain and Selvaraj, 1997). The most important development in this regard is the discovery of DNAbased marker technology referred to as Marker Assisted (Tanksley et al, 1996;Foolad et al, 2001). The approach of QTL mapping has become crucial to the use of DNA markers in the improvement of crops species (Ramchiary e al., 2007).…”
Section: Conventional Breeding Approaches For Enhancing Salt Tolerancmentioning
confidence: 99%